*Its important to use parenthesis.
first: the problem gives you the values for the variables
sec: place the values with the corresponding variables in the expression
(3)^2 - 2(3)(-2) + (-2)^2
Third: solve the expression according to order of operations >
PEMDAS > > > ( ), exponents, multiplication, division, addition & subtraction...
(3)(3) - 2(3)(-2) + (-2)(-2)
9 - 2(3)(-2) + 4
9 - 2(-6) + 4
9 + 12 + 4
21 + 4
= 25
2007-01-20 14:16:24
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
remember the order of operations Please Excuse My Dear Aunt Sally
first lets plug in the variables
3^2 - (2 * 3 * -2) + -2^2 do the parenthesis first
I like to do the multiplication from left to right because its simpler
-2 * 3 = 6 * -2 = 12
you now have 3^2 + 12 + -2^2
now do exponents
3^2 = 3 * 3 = 9
-2^2 = -2 * -2 = 4
you now have 9 + 12 + 4 I think you can take it from here.
2007-01-20 17:23:10
·
answer #2
·
answered by ikeman32 6
·
1⤊
0⤋
That's
(b-c)^2
Substituting
(3-(-2))^2 =
(3+2)^ = 5^2 = 25
2007-01-20 14:23:47
·
answer #3
·
answered by Joni DaNerd 6
·
0⤊
0⤋
question is attracting many diverse solutions because some imagine that b2 = 2 x b and some imagine b2 = b² . i go for b² !!!:--- b² - 2bc + c² (- 4)² - 2 (- 4) (- 2) + (- 2)² 16 - 16 + 4 4
2016-12-02 19:53:01
·
answer #4
·
answered by nastasi 4
·
0⤊
0⤋
b²-2bc+c² =
3² - 2.3.-2 + -2² = 9 + 12 - 4 = 17
The answer is 17.
><
2007-01-20 14:56:54
·
answer #5
·
answered by aeiou 7
·
0⤊
1⤋
b^2-2bc+c^2
=(b-c)^2 = (3-(-2))^2 = (3+2)^2 = 5^2 = 25
Sorry, but both your answers were wrong.
2007-01-20 14:07:44
·
answer #6
·
answered by ironduke8159 7
·
0⤊
0⤋
3^2-2(3)(-2)+(-2)^2
9+12+4
25
2007-01-20 14:09:09
·
answer #7
·
answered by Nick R 4
·
0⤊
0⤋
(3)^2-2(3*-2)+(-2)^2
9+12+4
21+4
25
2007-01-20 14:07:01
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
b^2-2bc+c^2
factor it to get
(b-c)^2
b = 3
c = -2
(3- (-2))^2
(5)^2
25
I guess both your answers were wrong.
2007-01-20 14:17:37
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋